BASICS OF BUSINESS START-UP - Pauceanu, Alexandrina Maria (ROUTLEDGE, 2026)
The Basics of Business Start-Up outlines the entrepreneurial journey from inception to start-up. Starting from the basic concepts and working through the start-up process step by step, the book is an indispensable guide both for would-be entrepreneurs and students on entrepreneurship/small business courses.Key features of this book include: A step-by-step, sequential approach, detailing the typical entrepreneurial journey. Non-technical introduction to the basic business functions, including budgeting, accounting, marketing, and more A readable and accessible beginner's guide to entrepreneurship and business start-up Written in a refreshingly personal style, this concise guide is the perfect starting point for anyone seeking to put their entrepreneurial ambitions into action.